Assessment of total mercury content in water of the Balkyldak Lake-reservoir, Pavlodar, Kazakhstan - Yapiev, Vadim; Inglezakis, V.J.; Korobeinyk, A.V.; Azat, S. (IOP Publishing, 2019)
This study aimed at determining the levels of total mercury in water samples collected in the vicinity of the Lake-reservoir Balkyldak in Pavlodar, Kazakhstan. Legacy of the chloralkali process in Pavlodar which involved the mercury cell method while producing a chlorine-free sodium hydroxide leads to serious environmental problems. At the time of the unit continuous operation in between 1971-1993 approximately 1000 metric tons of metallic mercury has been released into the wastewater holding pond at the chemical plant. For many years, mercury collected in the wastewater pond was a subject of the Kazakhstan sharply continental climate fluctuation and overflow to the Balkyldak Lake-reservoir, creating a significant mercury contamination issue for the whole region. Mercury emitted from industrial eluents in environment carries predominantly anthropogenic pollutants. Due to its natural cycle through atmosphere, water and soil in different forms prompts the widespread global mercury pollution. In present investigation, samples collected in a close proximity of the Balkyldak Lake were analyzed in respect to the geological location of collection.
Keywords: Research Subject Categories::MEDICINE